An Overview of Complications and Treatment Strategies in Periocular Dermal Fillers: A Literature Review - Ciesielska, Aleksandra; Sieradzka, Aleksandra; Szerej, Krzysztof; Kot, Alicja; Wojtczak, Marta; Myśliwiec, Natalia; Różycki, Adrian; Pniak, Michał; Miklis, Paweł; Mawlichanów, Maciej (Quality in Sport, 2025)
Introduction: The dermal filler market is a continuously expanding billion-dollar industry with the number of performed injections growing concurrently with the amount of post-injection complications. Most adverse events are mild and resolve spontaneously. Ischemic complications due to accidental intra-arterial filler injection may lead to skin necrosis and even irreversible vision loss. Aim of the study: This review aims to critically evaluate the use of dermal fillers in the periocular area, possible post-injection complications and treatment options for adverse events, providing further guidance for aesthetic medicine doctors. Methods: Databases such as PubMed, Medline and Research Gate were searched for articles published over the last 20 years. Results: Dermal fillers in the periocular area are often chosen over surgical procedures due to their efficacy and outstanding safety profiles. The reversing agent hyaluronidase causes hyaluronic acid fillers to be the primary choice for periocular filler injections. Post-injection complications after permanent fillers may require surgical excision. Conclusions: The periocular region is exceptionally demanding, requiring excellent anatomical awareness and proper administration techniques for uneventful procedures. Individually adjusted treatment plans and proper product selection is crucial. Doctors must follow preventative guidelines to minimize the complication risk, including aspirating before injecting the product, performing injections in the mid or deep dermal plane and administering small volumes with slow injections. Imaging techniques are significantly beneficial for minimizing the risk of the most severe ischemic complications.